2017
DOI: 10.1002/jca.21532
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange for perioperative management of patients with congenital factor XI deficiency

Abstract: TPE is an effective alternative presurgical hemostatic intervention in HEM-C with potentially lower risk of circulatory volume overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In a study by Alsammak et al 60% of a cohort of 28 patients with factor XI deficiency underwent surgical procedures without periprocedural hemostatic intervention. They also demonstrated successful therapeutic plasma exchange for four procedures [25]. Topical preparations of anti-fibrinolytics such as ε-amino caproic acid or tranexamic acid can also be used and avoids the systemic side effects such as thromboembolism [3].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Alsammak et al 60% of a cohort of 28 patients with factor XI deficiency underwent surgical procedures without periprocedural hemostatic intervention. They also demonstrated successful therapeutic plasma exchange for four procedures [25]. Topical preparations of anti-fibrinolytics such as ε-amino caproic acid or tranexamic acid can also be used and avoids the systemic side effects such as thromboembolism [3].…”
Section: Discussionmentioning
confidence: 99%
“…9 Therapeutic plasma exchange has also been reported as a means of avoiding volume overload, which can complicate traditional plasma infusion. 10 The liver appears to be a critical site for FXI production, and FXI deficiency may be corrected by orthotopic liver transplantation. 11,12 Unlike in Hemophilia A and B, routine prophylaxis for everyday activity is not required in individuals with FXI deficiency as they tend not to bleed spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred eighteen patients (88.1%) undergoing major surgery had good or excellent hemostatic control . Therapeutic plasma exchange has also been reported as a means of avoiding volume overload, which can complicate traditional plasma infusion . The liver appears to be a critical site for FXI production, and FXI deficiency may be corrected by orthotopic liver transplantation …”
Section: Discussionmentioning
confidence: 99%
“…The risk of functional refractoriness to simple plasma transfusion (or factor concentrates, if available) in inhibitor patients 18,19 makes TPE the favored pre-procedure intervention if there is any significant likelihood of bleeding, as is reflected in ASFA 2016 guidelines. 20 Alsammak et al 1 and Pagano et al 2 have pointed out the benefit of TPE in a subset of congenital FXI deficient patients pre-procedure. Acquired FXI represents an even stronger indication for TPE.…”
Section: Oncl Us I Onmentioning
confidence: 99%
“…Both Alsammak et al 1 and Pagano et al 2 have recently reported their use of pre-operative/pre-procedural therapeutic plasma exchange (TPE) for congenital FXI deficiency in the Journal of Clinical Apheresis. We would like to share our experience extending the use of TPE to a case of pregnancy-associated acquired FXI deficiency.…”
Section: Introductionmentioning
confidence: 99%